The Environmentally Tendentious Factor of Subtance Users (A Case Study on The Reason of The Substance Users in The Context of Interpersonal Communication in Jakarta) - Nurlina Rahman (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of research is to reveal the reason on how the substance users begin to use the substance (such as Narcotics, Alcohols, and other addictive substances), by understanding their environmental factor as one of the tendentious factors. The methodology used is the phenomenologic qualitative. The subjects are 16 people, who admitted using substance for the first time around the age of 10 to 16 years old, and one of them is using it since elementary school. The sampling technique used are the purposive and snow-ball sampling. The result of the research is to show on how substance abuse leads to addiction, supported by a tendentious factor, which is the environment, which triggers one to become a substance user. Hopefully, this research could give a better understanding for the society, especially for those who have been involved in the educational world or environment, so they can acknowledge the early symptoms of substance users, which has become a very concerning social phenomenon for Indonesian people, especially in Jakarta, as the capital city.